EFFECT OF ORGANIC AMENDMENT ON P RELEASE IN SOILS OF SOUTHWESTERN NIGERIA - Ige, D. V.; Adepetu, J. A.; Obi, O. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The study was conducted to assess the effect of amendment of soil with poultry manure on P fixing capacities of some soils and subsequently P uptake by maize. Eight soil series, representing the major soil types of southwestern Nigeria, were treated with five rates of P fertilizer and two rates of poultry manure in a laboratory incubation and greenhouse soil culture experiments. It was found that the addition of poultry manure significantly (at 1%) reduced the P-fixing capacities of the soils (by 23.2%). Increased plant uptake of P (by 44%) and consequently increased the dry matter yields of maize. It was concluded that amendment of soil with poultry manure could be used to decrease the P-fixing capacity of soils and thus enhance the P available to crops.